High Temporal Beta Diversity in an Ant Metacommunity, With Increasing Temporal Functional Replacement Along the Elevational Gradient - Nunes, Cássio Alencar; Castro, Flávio S.; Brant, Humberto S. C.; Powell, Scott; Solar, Ricardo; Fernandes, G. Wilson; Neves, Frederico S. (Frontiers in Ecology and Evolution, 2020)
Ecological communities vary considerably in space and time and understanding such changes has fundamental relevance for ecology and conservation sciences. Mountains provide an excellent scenario for studies addressing spatial and temporal variation, as they vary in conditions and resources in a small geographic region. Here, we aimed to understand the patterns of variation in ant metacommunity composition across time and along an elevational gradient in a tropical mountain, focusing both on the taxonomic and functional facets of diversity. We used a β-diversity metric and broke it into nestedness and turnover to estimate short-term temporal changes in ant metacommunity composition. We tested the following hypotheses: i. taxonomic and functional temporal β-diversity increase along the elevational gradient and ii. turnover is the main component driving taxonomic temporal β-diversity and nestedness for functional temporal β-diversity. Rejecting our first hypothesis, we found that both taxonomic and functional temporal β-diversity did not increase with elevation. Yet, the values were always high, indicating that both species and functional traits are highly variable over time. In accordance with our second hypothesis, we found that turnover was the main component of taxonomic β-diversity. Yet adding complexity to our hypothesis, the contribution of nestedness to functional β-diversity decreased with increasing elevation. These results suggest that at low elevations, the turnover in species composition may then cause changes in trait composition because of the loss of some traits, yet preserving the most common functions (nested functional communities), while at high elevations functional capabilities may change over time (turnover of traits). In the context of global warming, where tropical mountain insects are expected to change their distributional range upwards, it is extremely important to consider the importance of the turnover on the temporal variation in functional traits and functions of ant metacommunity at higher elevations.